Bezručův »Kovkop« - Všetička, František (Bohemistyka, 2017)
Composing the poem Metal Digger (Kovkop) Petr Bezruč used those tectonic means: repetition of a basic verb, enumerative listing, asked questions and mini-stories. A picture of blood takes an important role as well as the refrain and the title of the poem.